AI4PD—Towards a Standardized Interconnection of Artificial Intelligence Methods with Product Development Processes - Gerschütz, Benjamin; Götz, Stefan; Wartzack, Sandro (Applied Sciences, 2023)
The transformation of virtual product development to Digital Engineering (DE) requires the successful integration of Digital Engineering or data-driven methods into existing product development processes. Those methods allow for the analysis and usage of existing data. However, missing knowledge about these methods, as well as their performance or limitations, is a major burden for their application, especially in small and medium-sized enterprises. In order to close this gap, this paper proposes the AI4PD ontology, linking product development processes (PD) and Digital Engineering methods (AI). This knowledge representation gives companies an overview of the available methods to support them in selecting a suitable solution for their problems. The representation of AI4PD is performed in Protégé using the W3C standard OWL syntax. The opportunities of AI4PD are shown by a use case of identifying a DE-Method for predicting manufacturing possibilities based on test data and CAD files. Furthermore, after possible problems in existing product development processes are identified, AI4PD covers the necessary knowledge for a successful method of identification and integration to transform virtual product development to Digital Engineerin
Keywords: ontology; digital engineering; artificial intelligence; product development; formalisation; knowledge reuse; knowledge representation

A Machine Learning-Based Approach for Quick Evaluation of Live Simulations in Embodiment Design - Sauer, Christopher; Gerschütz, Benjamin; Bernsdorf, Jörg; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
Supporting product developers in early design phases with Live-Simulation can enhance the quality of early product designs. Live-Simulation can also facilitate a democratization of simulation and puts away pressure from simulation experts. In this paper, a machine learning based quick evaluation tool is proposed to support product developers in interpreting Live-Simulation results. The proposed tool enables a quick evaluation of the Live-Simulation results and enables product developers to further enhance their simulations. The tool is shown within a use case in bike rocker switch design.<br
Keywords: data-driven design; simulation-based design; structural analysis; machine learning; live-simulation

An adapted Method for Design Process Capturing to meet the challenges of digital product development - Gerschütz, Benjamin; Spießl, Bettina Vanessa Martina; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the International Conference on Engineering Design (ICED21), 2021)
n our modern, interconnected and globalized world, design is in motion, to adapt to new situations. But successful Design in Motion must be based on Processes in Motion. For a target-oriented adaptation of the processes to the new, challenging conditions, the as-is procedures must be captured and analysed. For this analysis, established capturing procedures from production or administration cannot be used due to some special features of design processes and workflows, which will be discussed in this contribution. To compensate for the weaknesses of existing methods, we propose an adapted method for holistic design process capturing. With the procedure, we want to enable an economic process analysis, which is crucial for small and medium-size companies in particular. To give an insight into the practical application of the method, we exemplarily analyse the process of a shaft construction and FEM-evaluation by two different employees. Based on this analysis and to verify the relevance of the presented approach, an evaluation with respect to the requirements is done. In our modern, interconnected and globalized world, design is in motion, to adapt to new situations. But successful Design in Motion must be based on Processes in Motion. For a target-oriented adaptation of the processes to the new, challenging conditions, the as-is procedures must be captured and analysed. For this analysis, established capturing procedures from production or administration cannot be used due to some special features of design processes and workflows, which will be discussed in this contribution. To compensate for the weaknesses of existing methods, we propose an adapted method for holistic design process capturing. With the procedure, we want to enable an economic process analysis, which is crucial for small and medium-size companies in particular. To give an insight into the practical application of the method, we exemplarily analyse the process of a shaft construction and FEM-evaluation by two different employees. Based on this analysis and to verify the relevance of the presented approach, an evaluation with respect to the requirements is don
Keywords: Process modelling; Organisation of product development; Digital/Digitised engineering value chanins

A Review of Requirements and Approaches for Realistic Visual Perception in Virtual Reality - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
The amount of new virtual reality input and output devices being developed is enormous. Those peripherals offer novel opportunities and possibilities in the industrial context, especially in the product development process. Nevertheless, virtual reality has to face several problems, counteracting reliable use of the technology, especially in ergonomic and aesthetic assessments. In particular, the discrepancies in perception between the real world and virtual reality are of great importance. Therefore, we discuss these most important issues of current virtual reality technology and highlight approaches to solve them. First, we illustrate the use cases of VR in the product development process. In addition, we show which hardware is currently available for professional use and which issues exist with regard to visual perception and interaction. Derived from the depiction of a perfect virtual reality, we define the requirements to address visual perception and interaction. Subsequently we discuss approaches to solve the issues regarding visual perception and evaluate their suitability to enhance the use of virtual reality technology in engineering design.
Keywords: Virtual reality; Visualisation; Visual perception; Eye tracking; Conceptual design

A semantic web approach for structuring data-driven methods in the product development process - Gerschütz, Benjamin; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the 32nd Symposium Design for X (DFX2021), 2021)
For the successful integration of data-driven methods in existing processes, it is first necessary to know these methods and their fields of application, potentials, and individual limits. This requires an easily accessible knowledge base. Depending on possible use cases and available data, this knowledge base should suggest methods that can lead to an optimization of the overall product development process. To prevent the knowledge base from being a rigid catalogue, it is essential to link it to the existing methods of the product development process. This contribution presents an approach based on the semantic web application Semantic MediaWiki, that ensures a connected representation of method knowledge and at the same time enables a link with use cases in the product development proces
Keywords: digital engineering; data-driven-method; design-process; semantic-web

Case-Based-Reasoning zur Vorhersage von Produkteigenschaften - Gerschütz, Benjamin; Götz, Stefan; Hörmann, Matthias; Wartzack, Sandro (Artificial Intelligence und Machine Learning in der CAE-basierten Simulation, 2023)

Digital Engineering Methods in Practical Use during Mechatronic Design Processes - Gerschütz, Benjamin; Sauer, Christopher; Kormann, Andreas; Nicklas, Simon J.; Götz, Stefan; Roppel, Matthias; Tremmel, Stephan; Paetzold-Byhain, Kristin; Wartzack, Sandro (Designs, 2023)
This work aims to evaluate the current state of research on the use of artificial intelligence, deep learning, digitalization, and Data Mining in product development, mainly in the mechanical and mechatronic domain. These methods, collectively referred to as “digital engineering”, have the potential to disrupt the way products are developed and improve the efficiency of the product development process. However, their integration into current product development processes is not yet widespread. This work presents a novel consolidated view of the current state of research on digital engineering in product development by a literature review. This includes discussing the methods of digital engineering, introducing a product development process, and presenting results classified by their individual area of application. The work concludes with an evaluation of the literature analysis results and a discussion of future research potentials. <br
Keywords: digital engineering; product development; data mining; machine learning; data-driven methods; system design; system integration; implementation; validation

Enabling Initial Design-Checks of Parametric Designs Using Digital Engineering Methods - Gerschütz, Benjamin; Bickel, Sebastian; Schleich, Benjamin; Wartzack, Sandro (Proceedings of the Design Society, 2022)
The world consequently gets faster, so does product development. Therefore, the stock of development and simulation data increases continuously. Unfortunately, inexperienced users cannot cope with the rising number of simulation requests in the time needed. Digital Engineering opens potentials to support the users with newly developed methods and tools. In this contribution, we present a method to assist designers, inexperienced in finite-element simulations to perform an initial check of changed parametric designs independently, quickly and with support in interpreting the results.<br
Keywords: digital design; data-driven design; supportive technologies; finite element method (FEM)

Konzept zur Verbesserung des realitätsgetreuen, visuellen Erlebens in virtuellen Umgebungen durch Eye-Tracking - Gerschütz, Benjamin; Fechter, Marius; Schleich, Benjamin; Wartzack, Sandro (Entwerfen Entwickeln Erleben in Produktentwicklung und Design 2019, 2019)
Ein positives Nutzungserlebnis (engl. User Experience) ist einer der Schlüsselaspekte erfolgreicher Produkte und damit auch die Grundlage für den wirtschaftlichen Erfolg des Unternehmens. Ergonomische Bedienbarkeit und ansprechende Gestaltung des Produkts haben hierauf einen starken Einfluss. Entwickler und Designer versuchen deshalb, dieses Erlebnis bereits in einer möglichst frühen Phase des Produktenwicklungsprozesses zu erfassen und zu bewerten. Ein in der Automobilbranche erfolgreich eingesetztes Werkzeug zur Bewertung des Nutzererlebnisses ist der Prototypenbau. Der Einsatz von Prototypen ist allerdings mit einem hohen zeitlichen und finanziellen Aufwand verbunden und erst in späteren Phasen des Produktentwicklungsprozesses möglich. Zu diesem Zeitpunkt können Produktänderungen einen hohen zeitlichen und finanziellen Mehraufwand bedeuten. Im Sinne des „Frontloadings“ ist es daher wünschenswert, für die Bewertung des Nutzererlebnisses früh zur Verfügung stehende, digitale Modelle zu nutzen. Damit können frühzeitig erste Erkenntnisse über das Nutzungserlebnis unterschiedlicher Konzepte in die Entwicklung des Produkts einfließen. Durch Einsatz von Methoden der Virtuellen Realität (VR) besteht die theoretische Möglichkeit, eine Bewertung des Produkts hinsichtlich Design und Ergonomie bereits in frühen Phasen des Produktentwicklungsprozesses durchzuführen. Jedoch besteht bei der visuellen Wahrnehmung von Größe, Distanz und Form in einem Head-Mounted Display (HMD), insbesondere im Nahbereich, eine signifikante Diskrepanz zwischen der virtuellen Darstellung eines Modells und dessen realen Aufbaus. Die Ursachen dieser Wahrnehmungsdiskrepanzen konnten in bisherigen empirischen Studien nicht exakt festgestellt werden. Im Allgemeinen werden diese mit fehlenden Tiefenhinweisen oder Abweichungen in zur Berechnung der visuellen Darstellung verwendeten Parametern, wie dem Sichtfeld oder dem Pupillenabstand, erklärt. Als Folge der vorhandenen Diskrepanz zwischen der gewünschten und der erzielten Darstellung, sind Ergebnisse aus virtuellen Studien, insbesondere für die Evaluierung ergonomischer Aspekte wie der Erreichbarkeit einzelner Bedienelemente, nur bedingt belastbar. Bisher verwenden die meisten HMDs eine vereinfachte Modellbildung zur Berechnung der visuellen Darstellung von Objekten. Es wird über die räumliche Lage des Kopfes auf die Positionen der Pupillen geschlossen, anstatt die exakten Pupillenpositionen heranzuziehen. Durch den Einsatz von Eye-Tracking innerhalb von HMD‘s eröffnet sich die Möglichkeit, die genaue Pupillenposition bei der Berechnung der visuellen Darstellung zu berücksichtigen. In diesem Beitrag wird ein Konzept vorgestellt, um das Potential des Eye-Trackings zur Erzeugung realitätsgetreuer, visueller Reize zu nutzen. Hierzu erfolgt die Betrachtung verschiedener Tiefenhinweise, die bei der Wahrnehmung im Nahbereich dominanten Einfluss besitzen und in bisherigen technischen Lösungen unzureichend angesprochen werden. Zusätzlich wird der Einfluss der Verzerrung der im HMD verbauten Linsen auf die Blickrichtungsabhängigkeit der Darstellung anhand eines Demonstrators zur Simulation von Linsenbrechung in HMDs aufgezeigt. Ausgehend von den beschriebenen Faktoren werden Lösungskonzepte präzisiert um die Einschränkungen zu überwinden. Der Beitrag endet mit einer Zusammenfassung sowie einem Ausblick auf nachfolgende Schritte zur Überwindung der Wahrnehmungsdiskrepanzen um ein realitätsgetreues, visuelles Nutzungserlebnis des Produkts zu ermögliche
Keywords: visuelle Wahrnehmung; Virtual Reality; Eye-Tracking; Head-Mounted-Display; User Experience

Ontology-based knowledge provision for decision support in product development - Pickel, Jessica; Gerschütz, Benjamin; Horber, Dennis; Götz, Stefan; Wartzack, Sandro (Proceedings of the 34th Symposium Design for X (DFX2023), 2023)
The product development process confronts engineers with numerous decision problems. In this context, it is a challenge to consider all underlying heterogeneous data sources and decision methods to avoid incorrect decisions. Regarding these issues, ontologies offer the possibility to represent knowledge in a structured and adaptable way. Thus, this contribution proposes a methodical conception of a product development ontology and a novel approach to support developers in solving interrelated decision problems by providing relevant knowledge in a target-oriented way. In addition, the application is demonstrated by an exemplary development scenario for the axle design of a micromobility solutio
Keywords: Ontology; product development process; decision-making; requirements management; knowledge management

PADDME—Process Analysis for Digital Development in Mechanical Engineering - Gerschütz, Benjamin; Consten, Yvonne; Götz, Stefan; Wartzack, Sandro (Processes, 2024)
Design processes are always in motion, since more and more data-driven methods are used for various design and validation tasks. However, small and medium enterprises especially struggle with enhancing their processes with data-driven methods due to a lack of practical and easy-to-use analysis and redesign methods which can handle design process characteristics. In this paper, we present PADDME, which stands for process analysis for digital development in mechanical engineering, as a novel method that, in contrast to currently available analysis methods, considers those design process characteristics with respect to the integration of data-driven methods. Furthermore, a novel technology-readiness framework for digital engineering is introduced. Using the PADDME method, an industrial case study on introducing data-driven methods into the design and evaluation process chain is presented. The usability and novelty of the method are shown by the case study. Thus, PADDME allows a detailed capturing of current design processes and paves the way for process optimisation through data-driven methods. PADDME is a valuable method for advancing digital mechanical engineering processes in small and medium enterprises, and future work will focus on refining and expanding its application and evaluation.<br
Keywords: digital engineering; design process; business process management; process evaluation; digitalisation; data-driven method

Potentiale von Simulationsdatenmanagementsystemen zur KI-gestützten Vorhersage und Bewertung von Produkteigenschaften - Gerschütz, Benjamin; Sauer, Christopher; Götz, Stefan; Hörmann, Matthias; Wartzack, Sandro (2023)

Towards Customized Digital Engineering: Herausforderungen und Potentiale bei der Anpassung von Digital Engineering Methoden für den Produktentwicklungsprozess - Gerschütz, Benjamin; Sauer, Christopher; Wallisch, Anne; Mehlstäubl, Jan; Kormann, Andreas; Schleich, Benjamin; Alber-Laukant, Bettina; Paetzold, Kristin; Rieg, Frank; Wartzack, Sandro (Stuttgarter Symposium für Produktentwicklung SSP 2021, 2021)
Mit dem Ziel, nationale und internationale Fachleute unterschiedlicher Disziplinen der Produktentwicklung aus Industrie und Wissenschaft in den Dialog zu bringen, organisiert der Verein zur Förderung produktionstechnischer Forschung e.V. und das Fraunhofer IAO gemeinsam mit dem Institut für Konstruktionstechnik und Technisches Design IKTD, dem Institut für Maschinenelemente IMA und dem Institut für Arbeitswissenschaft und Technologiemanagement IAT der Universität Stuttgart das Stuttgarter Symposium für Produktentwicklung SSP. Am 20. Mai 2021 findet das SSP zum sechsten Mal statt, diesmal als digitale wissenschaftliche Konferenz. Die Konferenz bietet Wissenschaftlern eine Plattform zur Präsentation und Diskussion ihrer neuesten Forschungsergebnisse im Bereich der Produktentwicklung und fördert so den interdisziplinären Wissenstransfer. Aufgerufen waren in der SSP 2021 Beiträge aus folgenden Kategorien: • Adaptive Bedienung für automatisiertes Fahren • Advanced Systems Engineering / Model-Based Systems Engineering • Agile Produktentwicklung • Design-Technik-Konvergenz • Digital Engineering • Innovations- und Technologiemanagement • Konstruktionsmethodiken • Leichtbau in der Produktentwicklung • Nachhaltige Produktentwicklung • Nutzerzentriertes Design • Wissensmanagement in der Produktentwicklung • Zuverlässige Produktentwicklung Im Plenum und vier Tracks mit jeweils drei Sessions werden 46 Beiträge präsentiert. Der Abstract der Keynote sowie die 45 Volltexte mit deutschen und englischen Abstracts sind in diesem Band zusammengefass
CRIS-Team Scopus Importer:2021-12-24
Keywords: Digital engineering; Industry 4.0; Product development

Umsetzung der Digitalisierung in der Produktentwicklung - Gerschütz, Benjamin; Götz, Stefan; Wartzack, Sandro (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2023)
Product development is undergoing a transformation. The paradigm of virtual product development is increasingly moving towards digital engineering. However, Small and Medium Enterprises (SMEs) face problems in optimising their processes by integrating data-driven methods due to a lack of approaches for focused process analysis and method identification. The proposed approach provides a structured process to support the integration of data-driven methods in product development. The focus is on finding use cases in existing and established processes and on selecting suitable methods.<br
Keywords: Digitalization; Process Transformation; Digital Engineering; Product Development Process; SME

Voraussetzungen für den Einsatz datengetriebener Methoden in der Produktentwicklung - Mehlstäubl, Jan; Nicklas, Simon; Gerschütz, Benjamin; Sprogies, Nicolai; Schleich, Benjamin; Lohner, Thomas; Wartzack, Sandro; Stahl, Karsten; Paetzold, Kristin (Proceedings of the 32nd Symposium Design for X (DFX2021), 2021)
Data mining and machine learning are successfully applied in many business areas such as marketing or production. Due to the increasing complexity in data and information flows and the large amount of data, data-driven solutions have also great potential in product development. Nevertheless, many companies are not able to integrate data-driven methods into their product development process. In order to support the application of data-driven methods, this paper identifies necessary prerequisites for their integration in product development. Based on a data analysis process, the prerequisites are elaborated and, subsequently, levers for their design are derive
Keywords: Data-driven Methods; Product Development; Data Mining; Machine Learning